2009
DOI: 10.1159/000209506
|View full text |Cite
|
Sign up to set email alerts
|

Sex Differences in Brain and Plasma β-Endorphin Content following Testosterone, Dihydrotestosterone and Estradiol Administration to Gonadectomized Rats

Abstract: Aims: The present study aims at evaluating the effect of a 2-week treatment with testosterone (T), dihydrotestosterone (DHT) and estradiol valerate (E2V) on brain and plasma β-endorphin (β-END) concentrations in gonadectomized rats of both sexes. Methods: Eight groups of female and 8 groups of male Wistar rats were included. For each sex, 1 group of gonad-intact and 1 group of gonadectomized rats were employed as controls (placebo). The other groups received subcutaneous T at the doses of 10 and 100… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(14 citation statements)
references
References 66 publications
0
14
0
Order By: Relevance
“…Conversely, Hammer et al (1993) found that hormone-depleted rats experienced reduced proenkephalin mRNA expression in various brain structures, and this reduction was not reversed with administration of DHT. Pluchino et al (2009) also found that depletion of gonadal hormones decreased brain beta-endorphin levels, and T administration conversely increased beta-endorphin levels in various brain areas and in the plasma of gonadectomized rats. In contrast, DHT treatment—using a 5 mg/kg/day regimen similar to that used in the present study—failed to restore beta-endorphin levels.…”
Section: Discussionmentioning
confidence: 78%
“…Conversely, Hammer et al (1993) found that hormone-depleted rats experienced reduced proenkephalin mRNA expression in various brain structures, and this reduction was not reversed with administration of DHT. Pluchino et al (2009) also found that depletion of gonadal hormones decreased brain beta-endorphin levels, and T administration conversely increased beta-endorphin levels in various brain areas and in the plasma of gonadectomized rats. In contrast, DHT treatment—using a 5 mg/kg/day regimen similar to that used in the present study—failed to restore beta-endorphin levels.…”
Section: Discussionmentioning
confidence: 78%
“…Indeed, electrical stimulation of the PAG induces a robust, opioid-dependent analgesia (Reynolds, 1969) that is attenuated by intra-PAG injection of the opioid receptor antagonist (−)-naloxone (Akil et al, 1976). Sex differences in pain sensitivity have been suggested to occur, in part, due to differences in endogenous opioid neurotransmission and in the circulation of steroid hormones (Micevych et al , 2003; LeResche et al, 2003; Smith et al, 2006; Pluchino et al 2009). Specifically, studies in rodents indicate significant sex differences in the anatomical and physiological characteristics of the PAG-RVM-spinal cord circuit.…”
Section: Mechanisms Of Analgesia: Endogenousmentioning
confidence: 99%
“…Testosterone is particularly important in the development of male-specific maturation in rodents and primates (Gupta et al, 1975; Sato et al, 2008). Although present in adult females, the concentration of circulating testosterone is much greater in adult male rodents (e.g., Pluchino et al, 2009) and primates (e.g., Muller et al, 2011), in whom it is linked to aggressive and reproductive behavior (Sato et al, 2008). Stålenheim et al (1998) reported that testosterone was associated with aggressive and antisocial behavior, which were more prevalent in alcoholic men with a family history of alcoholism.…”
Section: The Role Of Endogenous Neuroactive Steroids In Sex Differencmentioning
confidence: 99%